New Scenarios in Autonomy for Foreign Language Learning: Conference Summary and Reflections - Phil Benson; Marina del Carmen Chávez Sánchez; David McLoughlin; Jo Mynard; María de la Paz Adelia Peña Clavel (Studies in Self-Access Learning Journal, 2016)
The International Conference on Self-Access (Encuentro Internacional de Centros de Autoacceso, EICA) was held at the National Autonomous University of Mexico (Universidad Nacional Autónoma de México, UNAM) from the 4th to the 5th August, 2016. The conference theme in Spanish was Nuevos escenarios en torno a la autonomía del aprendizaje de lenguas extranjeras which translates as ‘New scenarios in autonomy for foreign language learning’ and was attended by approximately 280 delegates. Most delegates were based in Mexico and were mainly working in one of the numerous university or school-based self-access centres around the country. Others were classroom teachers interested in learner autonomy and how it can be fostered in their contexts.